Ecoturismo em Jaguarão / RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The present work presents the concern with the environment, using ecotourism as a conservation tool to be used as a way of sustainable exploitation of natural resources. For this reason it was possible to practice this segment in the municipality of Jaguarão, to raise awareness of the population as a way of sensitizing and valuing the environment in which they live. A bibliographical research was carried out through electronic means, academic articles and books in the environmental management segment for a better grounding in the subject, and field research, of an exploratory nature for practice and search of data of all the segments that are described and studied in it. It was observed that it is possible to contribute to the environment through the activities involved in the ecotourism segment, adding a new look at the relationship between man and nature, including daily concerns about the natural environment.
Keywords: Meio Ambiente; Ecoturismo; Instrumentos de Gestão; Jaguarão; Environment; Ecotourism; Management Tools; Jaguarão; CNPQ::CIENCIAS SOCIAIS APLICADAS